Microstructure and mechanical properties of a nanostructured Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr supersaturated solid solution prepared by high pressure torsion. (5th December 2017) - Sun, W.T.; Qiao, X.G.; Zheng, M.Y.; Xu, C.; Gao, N.; Starink, M.J.
Abstract: In this study, a solution-treated Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr (wt%) alloy was processed by high pressure torsion (HPT) at room temperature, with the aim of producing a material with exceptional mechanical properties. Transmission electron microscopy and X-ray diffraction line broadening analysis reveal that a nanostructured supersaturated solid solution with a mean grain size of 48 nm and high dislocation density of 4.7 × 10 14 m − 2 is achieved by HPT deformation. After HPT processing, the present solution-treated samples show finer grains and higher dislocation densities as compared to as-cast samples of this alloy, other solution-treated Mg-RE alloys and conventional Mg alloys deformed using similar HPT processing conditions. This could be attributed to retardation of the dislocation annihilation through enhanced solute-dislocation and/or dislocation-dislocation interactions. The higher dislocation density and nanosized grains within supersaturated solid solution cause the microhardness to increase to 126 HV, which is higher than that of the as-cast Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr (wt%) alloy processed by HPT, and is also higher than that of any conventional Mg-rich alloy deformed using HPT. Graphical abstract: Highlights: A nanostructured Mg-Gd-Y-Zn-Zr supersaturated solid solution is achieved by high pressure torsion at room temperature. High dislocation density and nanosized grains of supersaturated solid solution cause the microhardness increase to 126 HV. High solute content increases the dislocation density by enhancing solute-dislocation/dislocation-dislocation interactions.